HUBUNGAN ANTARA INVESTASI DAN KUALITAS ANAK USIA SEKOLAH PADA KELUARGA PETANI - Rahmiati, Tri Sari Asih; Puspitawati, Herien (Jurnal Ilmu Keluarga dan Konsumen, 2013)
Quality of human resources can be generated by child investment that conducted by parents. The study aimed to analyze correlation between investment and quality of school-aged children of farmer family in Cirebon District, West Java Province. Samples were farmer families who had children of school-age (11-12 years) in Buyut village that were selected by simple random sampling. This research involved 30 farmer families. Data was collected by interview with questionnaires and in-depth interview. Data was analyzed by correlation test. Child investment consist of material investment (family expenditure for child) and nonmaterial investment (time allocation, parent-child communication, and parenting pattern). Child quality consist of physical quality, cognitive quality, psicosocial quality, and child behavior. The results showed that child investment and child quality of farmer families were in the moderate category. Child investment will be better with increasing child’s age and parental education. Family investment especially nonmaterial investments correlated significantly with child quality. Child quality will be better with increasing nonmaterial investment who were done by family.